2016
DOI: 10.1002/eqe.2777
|View full text |Cite
|
Sign up to set email alerts
|

Shake table test and numerical study of self‐centering steel frame with SMA braces

Abstract: Summary Given their excellent self‐centering and energy‐dissipating capabilities, superelastic shape memory alloys (SMAs) become an emerging structural material in the field of earthquake engineering. This paper presents experimental and numerical studies on a scaled self‐centering steel frame with novel SMA braces (SMAB), which utilize superelastic Ni–Ti wires. The braces were fabricated and cyclically characterized before their installation in a two‐story one‐bay steel frame. The equivalent viscous damping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
84
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(88 citation statements)
references
References 46 publications
1
84
0
3
Order By: Relevance
“…2 These results suggest that reparability is not guaranteed for these "conventional" steel frames although they are expected to survive strong earthquakes without collapse. [14][15][16][17][18][19][20][21][22][23] The superelastic effect of a SMA enables up to 10% strain to be recovered upon unloading, and this high level of recoverable strain enables more compact self-centering components. 3 Self-centering structural systems provide effective solution to the issue of unacceptable permanent deformation.…”
Section: Introductionmentioning
confidence: 99%
“…2 These results suggest that reparability is not guaranteed for these "conventional" steel frames although they are expected to survive strong earthquakes without collapse. [14][15][16][17][18][19][20][21][22][23] The superelastic effect of a SMA enables up to 10% strain to be recovered upon unloading, and this high level of recoverable strain enables more compact self-centering components. 3 Self-centering structural systems provide effective solution to the issue of unacceptable permanent deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, beam‐to‐column connections, base isolators, and bridges …”
Section: Introductionmentioning
confidence: 99%
“…As such, the favorable features of superelastic SMAs attract increasing attention in the community of earthquake engineering. A variety of seismic‐resisting devices and structural components were developed during the last decades . Typical applications include dampers, isolators for buildings, restrainers for bridges, high‐performance bars, bolts and springs, and self‐centering braces …”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation based on the study in Japan further suggested that the threshold of residual interstory drift ratio in determining the repairability is 0.5%, raising the urgency of developing high‐performance braces to control peak seismic demands and to reduce residual deformation after earthquakes. SMABs could be a promising solution to this problem . For example, Dolce et al, among the earliest to successfully validate the potential of using SMAs to mitigate residual deformation for structures through shaking table tests of SMA braced reinforced concrete frame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation